Bright Sparklers fire and explosions: The lessons learned - Shaluf, Ibrahim M.; Ahmadun, Fakharul‐razi; Mustapha, Sa’ari; Mat Said, Aini; Sharif, Rashid (Emerald Group Publishing, 2002)
The fireworks industry is a dangerous business. Many disasters occur due to manufacturing and use of fireworks. It has been recorded that there have been 15 disasters resulting from fireworks worldwide. Malaysia has experienced such tragedies through a fire and explosion of Bright Sparklers fireworks factory. This paper summarizes the sequence of events which led to the Bright Sparkler disaster and proposes some lessons which could be learned from the experience. © MCB UP Limited.